17β-Estradiol Enhances Schwann Cell Differentiation via the ERβ-ERK1/2 Signaling Pathway and Promotes Remyelination in Injured Sciatic Nerves - Gu, Yun; Wu, Yumen; Su, Wenfeng; Xing, LingYan; Shen, Yuntian; He, Xiaowen; Li, Lilan; Yuan, Ying; Tang, Xin; Chen, Gang (Frontiers in Pharmacology, 2018)
Remyelination is critical for nerve regeneration. However, the molecular mechanism involved in remyelination is poorly understood. To explore the roles of 17β-estradiol (E2) for myelination in the peripheral nervous system, we used a co-culture model of rat dorsal root ganglion (DRG) explants and Schwann cells (SCs) and a regeneration model of the crushed sciatic nerves in ovariectomized (OVX) and non-ovariectomized (non-OVX) rats for in vitro and in vivo analysis, respectively. E2 promoted myelination by facilitating the differentiation of SCs in vitro, which could be inhibited by the estrogen receptors (ER) antagonist ICI182780, ERβ antagonist PHTPP, or ERK1/2 antagonist PD98059. This suggests that E2 accelerates SC differentiation via the ERβ-ERK1/2 signaling. Furthermore, E2 promotes remyelination in crushed sciatic nerves of both OVX and non-OVX rats. Interestingly, E2 also significantly increased the expression of the lysosome membrane proteins LAMP1 and myelin protein P0 in the regenerating nerves. Moreover, P0 has a higher degree of colocalization with LAMP1 in the regenerating nerves. Taking together, our results suggest that E2 enhances Schwann cell differentiation and further myelination via the ERβ-ERK1/2 signaling and that E2 increases the expression of myelin proteins and lysosomes in SCs to promotes remyelination in regenerating sciatic nerves.